Characterization and Endocytic Internalization of Epith-2 Cell Surface Glycoprotein during the Epithelial-to-Mesenchymal Transition in Sea Urchin Embryos - Wakayama, Norio; Katow, Tomoko; Katow, Hideki (Frontiers in Endocrinology, 2013)
The epithelial cells of the sea urchin Hemicentrotus pulcherrimus embryo express an Epith-2, uncharacterized glycoprotein, on the lateral surface. Here, we describe internalization of Epith-2 during mesenchyme formation through the epithelial-to-mesenchymal transition (EMT). Epith-2 was first expressed on the entire egg surface soon after fertilization and on the blastomeres until the 4-cell stage, but was localized to the lateral surface of epithelial cells at and after the 16-cell stage throughout the later developmental period. However, primary (PMC) and secondary mesenchyme cells (SMC) that ingress by EMT lost Epith-2 from their cell surface by endocytosis during dissociation from the epithelium, which was associated with the appearance of cytoplasmic Epith-2 dots. The cytoplasmic Epith-2 retained a similar relative molecular mass to that of the cell surface immediately after ingression through the early period of the spreading to single cells. Then, Epith-2 was completely lost from the cytoplasm. Tyrosine residues of Epith-2 were phosphorylated. The endocytic retraction of Epith-2 was inhibited by herbimycin A (HA), a protein tyrosine kinase (PTK) inhibitor, and suramin, a growth factor receptor (GFR) inhibitor, suggesting the involvement of the GFR/PTK (GP) signaling pathway. These two GP inhibitors also inhibited PMC and SMC spreading to individual cells after ingression, but the dissociation of PMC and SMC from the epithelium was not inhibited. In suramin-treated embryos, dissociated mesenchyme cells migrated partially by retaining their epithelial morphology. In HA-treated embryos, no mesenchyme cells migrated. Thus, the EMT occurs in relation to internalization of Epith-2 from presumptive PMC and SMC.